Pengaruh Pengetahuan Peraturan Perpajakan Dan Ketegasan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Kecamatan Lembang - Angelina Simanjuntak; Herold Moody Manalu (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The aim of this research is to examine the relationship between UMKM taxpayer compliance in Lembang Regency and two factors, namely understanding tax regulations and the severity of tax sanctions. This research uses a qualitative approach by distributing questionnaires. The target demographic is UMKM taxpayers in Lembang Regency, and the research sample consists of 50 companies. Descriptive statistics, multiple linear regression analysis, classical assumption analysis, hypothesis testing, and coefficient of determination are just some of the tools used in this data analysis. The findings of this research highlight the importance of thorough knowledge of tax regulations and strict tax sanctions in ensuring UMKM taxpayer compliance in Lembang Regency.